Kinesiophobia in rheumatoid arthritis patients: Relationship with quadriceps muscle strength, fear of falling, functional status, disease activity, and quality of life - İlkay Baysalhan Öztürk,; Yeşim Garip,; Filiz Sivas,; Merve Parlak Özden,; Hatice Bodur, (Archives of Rheumatology, 2021)
Objectives: This study aims to determine the frequency of kinesiophobia in rheumatoid arthritis (RA) patients and to evaluate the relation of kinesiophobia with the knee range of motion (ROM), quadriceps muscle strength, fear of falling, functional status, disease activity, depression, and quality of life. Patients and methods: Between September 2018 and September 2019, a total of 100 RA patients (25 males, 75 females; mean age: 56.1±9.3 years; range, 32 to 69 years) and 50 healthy controls (14 males, 36 females; mean age: 54.6±9.8 years; range, 30 to 69 years) were included. Disease activity was evaluated using the Disease Activity Score 28 (DAS28), and functional status using the Health Assessment Questionnaire (HAQ). Pain severity was measured using the Visual Analog Scale (VAS). Tampa Kinesiophobia Scale (TKS) was used to evaluate kinesiophobia. Quadriceps muscle strength and knee ROM measurements of two extremities were recorded. Depression was evaluated using the Beck Depression Inventory (BDI), fear of falling by Falls Efficacy Scale (FES) and quality of life using the Short Form-36 (SF-36). Results: The rate of kinesiophobia was 70% in RA patients and 12% in controls, indicating a higher rate in RA patients, compared to controls (odds ratio [OR] = 44.861, 95% confidence interval [CI]: 42.571-49.052; p<0.05). This rate was 76% in females and 52% in males. Regression analysis revealed that the number of swollen and tender joints, DAS28, VAS-pain, and HAQ scores were positively associated with the TKS scores (p<0.05). Quadriceps muscle strength and knee flexion were negatively associated with the TKS scores (p<0.05). The TKS was significantly correlated with FES and BDI (p<0.05). The TKS was negatively correlated with SF-36 subscales (p<0.05). Conclusion: Kinesiophobia is common in RA patients. Our study is the first to evaluate the frequency of kinesiophobia in RA patients and to show pain level, disease activity, functional status, knee flexion ROM, and quadriceps muscle strength are effective on kinesiophobia. Kinesiophobia is also associated with fear of falling and depression, negatively affecting the quality of life in terms of physical, emotional, social and mental functions. Therefore, evaluating kinesiophobia and developing targeted treatment approaches seem to be useful in increasing the quality of life in RA.